Resilient in adversity: Innovative treatment support interventions in facilitating ART adherence among young adults living with HIV in the informal settlements of Kibera, Nairobi - Odylia Muhenje; Charles O. Olungah; Dalmas O. Omia; Raphael O. Ondondo; Paul Waswa; Adelaide Lusambili (PLoS ONE, 2026)
Background Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) poses significant health challenges. Despite ongoing efforts to scale up Antiretroviral therapy (ART) to save lives from AIDS-related morbidity and mortality,adherence among young adults remains low at 65% in sub-Saharan Africa. Aim Our study aimed to inform the development of youth-friendly, context-sensitive programs that are both scalable and sustainable in urban informal settlements. This paper presents findings on youth facilitators to ART adherence in Kibera informal settlement. Setting The study was conducted in Nairobi urban informal settlement of Kibra, Nairobi county, Kenya. Methods We utilized in-depth interviews (n = 25) and key informant interviews (n = 10) to collect data on faciliators to ART adherence among purposively selected eligible partcipants. Thematic analysis framework was employed to analyze the data. Results HIV adherence facilitators encompassed patient-related factors like self-acceptance and open disclosure, health system factors such as accessibility, provider relationships, and patient reminders, and socio-economic aspects including support groups, education awareness, family support, and economic empowerment. Conclusions The findings emphasize the need for tailored, age-appropriate, and context-specific interventions in informal settlements to enhance HIV adherence. Fostering self-acceptance, creating an enabling environment through youth friendly services, improving provider-patient relationships, and leveraging social support systems such as peer groups and educational initiatives are essential strategies. Integrating these elements into programmatic and policy frameworks will ensure that interventions resonate with the unique realities of this populationpromoting sustainable adherence outcomes. Contribution The findings will provide a foundation for developing context-sensitive interventions and programs to improve adherence in similar settings.